AB0747 RESPONSE TO SECUKINUMAB AMONG NAIVE AND BIOLOGICALLY EXPERIENCED PATIENTSIN PSORIATIC ARTHRITIS. (June 2019) - Farrukh, Shehla; Riordan, Ann O.; Haroon, Muhammad; Adeeb, Fahd
Abstract : Background: Secukinumab is a recombinant human monoclonal immunoglobulin IgG antibody that selectively targets IL-17A and blocks its interaction with the IL-17 receptor. Inhibition of the downstream effects of this proinflammatory cytokine thereby interferes with key psoriasis disease pathways while promoting normalization of immune function and skin histology. Objectives: The aim of the study was two-fold; firstly, to compare the response to Secukinumab in psoriatic arthritis (PsA) patients who were biologically naive and experienced, and secondly to compare the response between smokers and non-smokers. Methods: In collaboration with the National Psoriatic arthritis Registry of Ireland, patients who were diagnosed and treated as PsA at University Hospital Kerry between March 2017 and October 2018 were included in this population-based cohort study.Patients demographic, clinical characteristics, treatment strategies (including response rates and adverse effects) were captured at baseline and at follow-up outpatient visits. Results: A total of 96 patients were identified and included in the study (mean age of 56.6 years; male to female ratio of 1:1, 49 males, 47 females). Of these patients, 15 received Secukinumab (7 biologically-naive patients, 8 patients with previous treatment failure to anti-TNF agents (3 patients received one anti-TNF, 5 received two different anti-TNFs). In the biologically-naive group, 5 patients(71%) had completeresponse to Secukinumab, one patient (14.3%) had complete improvement of joint symptoms but remained fatigued (high BRAF score) while 1 patient (14.3%) had no improvement. All 7 of these patients were exposed to cigarette smoking (6 current smokers, one ex-smoker). In patients who previously failed anti-TNF, five(62.5%) remained symptomatic (tender & swollen joints, PROMs and BRAF score remained high) despite treatment with Secukinumab. Only three patients (37.5%) responded well to treatment. Two of the eight patients never smoked (both did not respond to Secukinumab) while the other 6 patients (3 responded, 3 had no response) were ex-smokers. Conclusion: In our study, Secukinumab demonstrated better response to the biologically-naive PsA patients, while smoking did not increase the risk of disease activity among PsA patients receiving Secukinumab. Disclosure of interests: None declared